Impact of alcohol intake on the relationships of uric acid with blood pressure and cardiac hypertrophy in essential hypertension. Issue 5 (November 2016) - Seki, Shingo; Oki, Yoshitsugu; Tsunoda, Seiko; Takemoto, Tomoyuki; Koyama, Tatsuya; Yoshimura, Michihiro
Abstract: Background: Hyperuricemia, which is frequently associated with hypertension, can be caused by alcohol intake. To date, limited data have shown the link between alcohol intake and hyperuricemic hypertension. Methods: We retrospectively examined the influence of alcohol intake on the relationship between the uric acid level and blood pressure or cardio-metabolic parameters in 171 untreated non-failing hypertensive patients (mean 59.3 ± 10.7 years). Cross-sectional analysis was separately performed in regular alcohol drinkers (more than 25 g/day ethanol, n = 74, 82.4% men) and non-drinkers ( n = 97, 33.0% men). Results: Diastolic blood pressure was significantly higher in drinkers than in non-drinkers (101.6 ± 11.5 mmHg vs. 96.8 ± 8.2 mmHg, p < 0.01). Estimated glomerular filtration rate (80.4 ± 14.7 mL/min/1.73 m 2 vs. 80.0 ± 17.8 mL/min/1.73 m 2 ) and body mass index (BMI, 24.7 ± 4.4 kg/m 2 vs. 24.8 ± 4.2 kg/m 2 ) were similar in the two groups. In the drinker group, the uric acid level (mean 6.3 ± 1.7 mg/dL) was positively correlated with both systolic and diastolic blood pressures ( r = 0.270/ p = 0.020 and r = 0.354/ p = 0.0020, respectively), and with the markers of cardiac hypertrophy, including electrocardiographic voltage (V1 S + V5 R, r = 0.244/ p = 0.042) and echocardiographic left ventricular mass index ( r = 0.270/ p = 0.026). These correlations were also observed in the male drinker sub-group. In the non-drinkers, the uric acid level (mean 5.0 ± 1.4 mg/dL) was positively correlated with BMI ( r = 0.369/ p = 0.0002) but not with blood pressure or the markers of cardiac hypertrophy. Conclusions: The results suggest that the role of uric acid in blood pressure might differ between hypertensive drinkers and non-drinkers. In regular alcohol drinkers, there was a positive association of uric acid level with blood pressure and the severity of cardiac hypertrophy. In non-regular drinkers, an increased uric acid level is likely to be closely associated with increased BMI.